Spatial Differentiation of the Standard of Living in the Population as a Representation of Disproportions in Socioeconomic Development: A Case Study of Belgorod Oblast - Chugunova, N. V.; Likhnevskaya, N. V. (Regional research of Russia, 2019)
The article considers spatial differences in the standard of living in the population on a regional scale within Belgorod oblast; along with other regions, this federal subject is exposed to federal reforms being implemented in the socioeconomic sphere. The study determines approaches to analyzing the standard of living (SOL) and establishes its main measures. Intraregional differentiation of the SOL components is investigated, extensively using GIS technologies. The component-based study has revealed that the extent of disproportions among municipalities is particularly large for social and socioeconomic indicators, representing a decline in the number of enterprises in the social sphere and the number of employed persons in countryside. Agroholdings were found to play a significant role in the change in SOL indicators and settlement pattern of the rural population. The outcome of the research is a typology of municipal and urban districts according to their level of socioeconomic development based on the synthetic SOL measure, which has brought to light extensive intraregional disproportions. It has been determined that the high level of development is specific to the regional center (Belgorod) alone.